1998
DOI: 10.1021/ar970154s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Detoxification of Nerve Agent VX

Abstract: Yu-Chu Yang was born in China, grew up in Taiwan, and has lived in the United States since 1969. She holds a B.S. degree (1969) in Chemical Engineering from the National Taiwan University and a Ph.D. (1974) in Physical Chemistry from Tulane University. After graduation, she worked for Exxon Corp. both in Louisiana and in New Jersey for nearly 6 years. In 1983, she began research work in the decontamination of chemical warfare agents at the U.S. Army Edgewood Research, Development and Engineering Center in Mary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
388
3
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(403 citation statements)
references
References 23 publications
10
388
3
2
Order By: Relevance
“…As part of our on-going investigations geared towards harnessing the twin properties of electroactive amino-substituted transition MPc (notably, the CoTAPc) complexes and CNTs [23] and [24], this work is aimed at investigating the electrochemical and The serious threats posed to the society by terrorists have made the fast detection of organophosphates based chemical warfare agents (CWAs), especially those of the V-type nerve agents and their sulfhydryl hydrolysis products [25] and [26] (Table 1) a major global concern. Thus, in this work, we investigated the possible applications of the modified BPPGEs as viable devices for the study of the electrocatalysis and sensing of sulfhydryl degradation products of CWAs, i.e., those of the V-type nerve agents, diethylaminoethanethiol (DEAET) and dimethylaminoethanethiol (DMAET) ( [25] and [26]. These sulfhydryl degradation products are far more stable in the environment than their parent V-type nerve agents, meaning that they can be easily utilised to provide a reliable indication of the parent nerve agents.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our on-going investigations geared towards harnessing the twin properties of electroactive amino-substituted transition MPc (notably, the CoTAPc) complexes and CNTs [23] and [24], this work is aimed at investigating the electrochemical and The serious threats posed to the society by terrorists have made the fast detection of organophosphates based chemical warfare agents (CWAs), especially those of the V-type nerve agents and their sulfhydryl hydrolysis products [25] and [26] (Table 1) a major global concern. Thus, in this work, we investigated the possible applications of the modified BPPGEs as viable devices for the study of the electrocatalysis and sensing of sulfhydryl degradation products of CWAs, i.e., those of the V-type nerve agents, diethylaminoethanethiol (DEAET) and dimethylaminoethanethiol (DMAET) ( [25] and [26]. These sulfhydryl degradation products are far more stable in the environment than their parent V-type nerve agents, meaning that they can be easily utilised to provide a reliable indication of the parent nerve agents.…”
Section: Introductionmentioning
confidence: 99%
“…The discussion of this important subject is beyond the scope of this review, but it may be found elsewhere. [123][124][125][126] …”
Section: Opcs As Chemical Warfare Agentsmentioning
confidence: 99%
“…17 Hydrolysis of VX, along with other aspects of detoxification, was recently reviewed. 265 A summary of key hydrolysis pathways is shown in Scheme 6. One reference gives hydrolysis rate constants for VX as 8.4 × 10 -3 h -1 ([VX] 0 ) 2%) and 12.1 × 10 -3 h -1 ([VX] 0 ) 0.5%) in distilled water at 21°C.…”
Section: S-[2-[bis(1-methylethyl)amino]ethyl] O-ethyl Ester; Iupac Namentioning
confidence: 99%